Adjuvant Maneuvers for Residual Curvature Correction During Penile Prosthesis Implantation in Men with Peyronie's Disease. (November 2015) - Berookhim, Boback M.; Karpman, Edward; Carrion, Rafael
Abstract: Introduction: The surgical treatment of comorbid erectile dysfunction and Peyronie's disease has long included the implantation of an inflatable penile prosthesis as well as a number of adjuvant maneuvers to address residual curvature after prosthesis placement. Aim: To review the various surgical options for addressing curvature after prosthesis placement, with specific attention paid to an original article by Wilson et al. reporting on modeling over a penile prosthesis for the management of Peyronie's disease. Methods: A literature review was performed analyzing articles reporting the management of penile curvature in patients undergoing implantation of an inflatable penile prosthesis. Main Outcome Measures: Reported improvement in Peyronie's deformity as well as the complication rate associated with the various surgical techniques described. Results: Modeling is a well‐established treatment modality among patients with Peyronie's disease undergoing penile prosthesis implantation. A variety of other adjuvant maneuvers to address residual curvature when modeling alone is insufficient has been presented in the literature. Conclusions: Over 20 years of experience with modeling over a penile prosthesis have proven the efficacy and safety of this treatment option, providing the surgeon a simple initial step for the management of residual curvature after penile implantation which allows for the use of additional adjuvant maneuvers in those with significant deformities.Berookhim BM, Karpman E, and Carrion R. Adjuvant maneuvers for residual curvature correction during penile prosthesis implantation in men with Peyronie's disease. J Sex Med 2015;12(suppl 7):449–454.